Alguns métodos de resolução geométrica de equações do segundo e terceiro graus - Sousa, Erika Eduarda Araújo (2019)
In this work we present some geometric methods to solve quadratic equations: methods of Euclids, Descartes, Leslie/Carlyle, Staudt and method of the tangens circles. We also present the method of Omar Khayyam to find the positive solution of a cubic equation.